Efficient PKC inhibitor screening achieved using a quantitative CE-LIF assay - Binh Thanh Nguyen; Park, Min; Pyun, Jae-Chul; Yoo, Young Sook; Kang, Min-Jung (John Wiley & Sons Ltd., 2016)
An assay for protein kinase C delta (PKC delta) activity based on the quantification of a synthetic substrate using capillary electrophoresis with laser-induced fluorescence detection was developed. The peptides labeled with fluorescein isothiocyanate F-ERK (where ERK is extracellular signal-regulated kinase) and the phosphorylated form, P-F-ERK, were utilized for the method development and validation. The migration time of F-ERK and P-F-ERK were 6.3 +/- 0.1 and 8.7 +/- 0.2 min, respectively. LOD and LOQ values of F-ERK were 2 and 6 ng/mL and those of P-F-ERK were 4 and 12 ng/mL. The correlation coefficients obtained from two standard curves were approximately 0.99. The reproducibility and accuracy of the method for F-ERK ranged 1.5-4.7 and 86-109%, respectively, and those for P-F-ERK were 1.6-6.1 and 93-109%, respectively. The activity of PKC delta was studied in vitro using the human gastric cancer cell line MKN-1. The use of PKC delta inhibitor candidates, including G.6983, bisindolylmaleimide II, staurosporine, and rottlerin in the assay resulted in IC50 values of 50 nM, 15 nM, 795 nM, and 4 mu M, respectively. Comparison of our assay with a commercial PKC kit revealed that our assay is more adaptable to differing enzyme isoforms. This method has potential for high throughput screening for kinase inhibitors as part of a drug discovery program.